Aplikasi Pembelajaran Aksara Jepang Berbasis Android - Sumarlin, Herlan Zendy; Sutanto, Teguh; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: Reading and writing in Japanese isn't easy for foreigners especially Indonesian because of its script that were very different from Indonesian that uses latin script. It is said that the Japanese writing system is one of the most complex writing system in the world. Japanese language uses mixed of three script, the hiragana, katakana, and the chinese characters. We don't have a choice what script we wanted to use because each script has their own uses so even in a simple sentence, that three script could appear together. Because of that, in order to be able to read and learn Japanese language, one should learn the three of Japanese script.While Japanese learn these script at school, Indonesian should be helped by good teaching materials and peripherals. One of the peripherals that could aid the Indonesian to learn the script effectively is the touch screen smartphone. Smartphone as an aid peripheral has a benefit because it's cheap, fast, and easy to use. It has a touchscreen to aid the user how to write the script because the way to write the script matters.The evaluation showed that this application could provide convenience and greater good to aid Indonesian to learn the three Japanese scripts.